Dizziness - Murdin,L; Seemungal,BM; Bronstein,AM (Medicine (United Kingdom), 2016)
© 2016 Elsevier Ltd Dizziness and vertigo are common symptoms. Because there are effective treatments for vestibular disorders, it is always important to make an accurate diagnosis. In acute vertigo, expert clinical assessment is critically important in discerning stroke from non-stroke causes because stroke-protocol brain magnetic resonance imaging results, including diffusion-weighted imaging, can be falsely negative in the first 24 hours. It follows that acute medical services must have access to clinicians expert in assessing acute vertigo. Expertise in clinical examination and the interpretation of findings requires appropriate training, but in this article we outline the basic diagnostic and therapeutic approach to patients with dizziness.